Information revolutions and spreading of communication channels: overview of divergence and/or convergence of the media (Libellarium: journal for research in the field of information and related sciences, 2012)
The paper provides an overview of the so-called information revolutions, with a special emphasis on the spreading of communication channels. The notion 'information revolution' is used conditionally – not in the sense of disruptive changes in communication models, but in the sense of expansion of communication possibilities.The revolutions were identified using Irving E. Fang's criteria. He defined six revolutions: writing, printing, mass media, using media for entertainment, the 'toolshed' (now called 'home'), and the Information Highway. The paper presents the basic media in each of the revolutions, questions the very current issues of convergence (as some modern scholars consider the term convergence to be more appropriate than the term revolution), and divergence of media, and special attention is paid to the social context that lead to particular revolutions.The central conclusion is that information revolutions were not the time of replacing the old media with the new, but the times of condensation of communication possibilities. During those times the new media joined the existing types, not replacing them but co-existing. They faded out gradually or disappeared only over extended periods of time.
Keywords: information revolutions; media; convergence; divergence; communication